Urgensi Pendidikan Keluarga Pada Anak Usia Sekolah Dasar Perspektif Al-Quran Dan Hadis - Taufiq, Tugastono; Musthofa, Tulus; Saidah , Nur (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2023)
Education within the family environment plays a strategic role in shaping the character and potential of children from an early age. This encompasses the development of intelligence, morality, personality, and social readiness. The objective of this writing is to understand the urgency or importance of family education for elementary school-aged children. This article also discusses the crucial role of parents in developing children's social and emotional behavior, as well as describing the stages of physical and psychological development in elementary school-aged children. This research employs a literature review method with a qualitative approach to explore the concept of family education, particularly in the context of educating children aged 6-12 years old. This concept is expressed through the teachings of the Quran and the hadiths of Prophet Muhammad (SAW) as the primary foundation in Islamic education. The research findings highlight the importance of the role of parents as role models and examples for children. Good education in the family environment has a positive impact on the development of children, creating individuals who are mature, disciplined, and responsible. In this context, effective communication between parents and schools is key, as well as the importance of positive influence in shaping good values from an early age. Therefore, family education in Islam holds high significance in shaping a morally, culturally, and spiritually strong future generation.